ANALISIS PENYUSUNAN LAPORAN KEUANGAN UMKM BATIK SARIWARNI BERDASARKAN SAK-EMKM - Anisa Uun Purnamasari; Dinda Nur Aini; Nidya Tahta Nur Azizah; Riza Dessy Nila Ayutika (Jurnal Proaksi, 2023)
Sariwarni Batik is part of UMKM that have the potential to grow and develop. However, in its business operations, financial recording and reporting are still carried out manually. The goal is to find out and help compile Batik Sariwarni financial statements based on SAK EMKM. Using the description research method, because information or data sources come from interviews directly to business owners. Interactive analysis is used as a data analysis model consisting of 3 stages, namely reducing data, presenting data, and concluding. Research results were obtained that Batik Sariwarni has not applied financial accounting standards in recording transactions, as well as SAK EMKM in the composition of financial statements. Based on accurate stages and accural basic approach.